(untitled) (Eurasian Medical Research Periodical, 2026)
This paper examines the problem of the development of leukosis, or blood cancer, in children, which accounts for a significant proportion of all pediatric oncological diseases. In Uzbekistan, leukosis and other oncohematological diseases are considered serious and pressing issues and require special attention from the healthcare system. The paper reviews the main causes of this pathology, including mutations and disruptions of hematopoiesis in the bone marrow due to genetic predisposition, exposure to chemical carcinogens, viruses and radiation. The article also briefly presents current data on the prevalence of leukosis both in Uzbekistan and globally, allowing an assessment of the scale of the problem.